Dampak Kebijakan Moneter terhadap Ketimpangan Distribusi Pendapatan Riau: Penelitian - Yuda Apriansyah; Darmayuda; Supriani Sidabalok (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of monetary policy on income distribution inequality in Riau Province. Monetary policy is represented by two main variables: real interest rate and inflation rate. The data used are annual secondary data from 2005 to 2023, obtained from the Central Statistics Agency (BPS) and Bank Indonesia. This research employs multiple linear regression to examine the relationship between the independent variables and the Gini index as a proxy for income inequality. The results indicate that the real interest rate has a positive effect on income inequality, suggesting that an increase in the interest rate tends to widen the income gap. In contrast, inflation does not have a impact on inequality in Riau during the observation period. The coefficient of determination (R-squared) is 33.18%, indicating that the model explains a portion of the variation in income inequality, while the rest is influenced by other factors outside the model. This study recommends that monetary policy should consider its distributional effects and be integrated with fiscal policy to promote more equitable economic outcomes.